Metal Anticancer Complexes – Activity, Mechanism of Action, Future Perspectives. Issue 12 (6th March 2017) - Alessio, Enzo; Guo, Zijian
Abstract : Guest editors Enzo Alessio and Zijian Guo present an overview of the topics reported in the papers of this issue, listing the general trends that dominate the field of metal anticancer complexes. They provide an analysis of the development of this area of chemistry since its official start about 50 years ago, present the status quo and offer insights into future perspectives. Abstract : Guest Editors Enzo Alessio and Zijian Guo describe the trends in the field of metal anticancer complexes that emerge from this thematic issue.